Efek Penambahan Fraksi Semi Polar Ekstrak Metanolik Herba Phyllanthus niruri, L. terhadap Daya Hambat Amoxicillin dan Chloramphenicol pada Staphylococcus aureus dan Escherichia coli - Wigdio Almadany Susilo (Jurnal Kedokteran Komunitas, 2019)
Introduction: One method to increase the effect of antibiotics is to combine it with a herb that is suspected have an antibiotics activity, such as Phyllanthus niruri, L. The crude extract of Phyllanthus niruri, L. was found have an antagonistic and synergistic effect with amoxicillin against Escherichia coli and Staphylococcus aureus. This study aims to separate the herb compounds using fractionation, and then phytochemical test, Zone of Inhibition (ZOI) test on the semi-polar fractions (F14-18) with amoxicillin and chloramphenicol on S. aureus and E. coliMethods: The effect of herbal combination with antibiotic was measured with ZOI test using the Kirby-Bauer method. The clear zone formed was measured with a ruler, and the results were interpreted based on the Ameri-Ziaei Synergic Test for Double Antibiotic (AZDAST) method. Phytochemical tests were carried out to compare the active compound of the herbal fraction using the Thin Layer Chromatography (TLC).Results: All semi-polar fractions (F14-F18) of methanolic extract of Phyllantus niruri L. formed a clear zone against S. aureus, but not E. coli. The ZOI measurements’ mean of  F16 combined with amoxicillin against S. aureus was 11 ± 1 mm, and it was greater than the antibiotic and herb mean which is 2,33 ± 4,04  and 9,33 ± 0,57. Phytochemical test results showed F16, 17, and 18 might contain saponin or alkaloid as an active antibiotics compound.Conclusion: Semi-polar fractions (F14-18) methanolic extract of Phyllanthus niruri, L. had antibiotics activity againts S. aureus, but not E. coli. Combination with F16 had a synergistic effect which was increased the effects of amoxicillin. F16 might contains saponin.Keywords: Phyllanthus niruri, L., Amoxicillin, Chloramphenicol, Phytochemical Test, ZOI, Combination of Antibiotics and Herb